Carbon footprint and embodied energy of PVC, PE, and PP piping: Perspective on environmental performance. (December 2020) - Alsabri, Amzan; Al-Ghamdi, Sami G.
Abstract: This study is aimed at comparative data analysis of three types of polymers i.e. Polyvinylchloride (PVC), Polyethylene (PE) and Polypropylene (PP). These polymers are widely used in Piping, water sanity, and medical industries. Polypropylene is highly thermal resistant and can withstand much higher temperatures than PVC. Literature review was done to analyze Life cycle assessment and carbon footprint of these plastic production processes to find the environmental impact that contributes to global warming. However, PVC has higher energy consumption and CO2 gas emission that shows its high potential in global warming than other plastics. Moreover, the recycling of PVC has shown significant contributions in lowering the effect on climate change. This study also focuses on the industries which produces significant CO2 emissions into environment and how we can reduce these emissions in most appropriate ways.